Effects of moderate electric fields in beta-lactoglobulinthermal denaturation: structural changes and binding properties - Rodrigues, Rui Miguel Martins (2019)
This study was supported by the Portuguese Foundation for Science and Technology (FCT) under the scope of the strategic funding of UID/BIO/04469/2019 unit and BioTecNorte operation (NORTE-01-0145-FEDER-000004) funded by the European Regional Development Fund under the scope of Norte2020 - Programa Operacional Regional do Norte. Rui M. Rodrigues gratefully acknowledge FCT for their financial grant with reference SFRH/BD/110723/2015.